Socioeconomic and Obstetric Risk Factors for Preterm Labour Among Pregnant Women in Wasit General Hospitals - Anwer Hussain, Zaman; ALRubayae, Bushra (Journal of Neonatal Surgery, 2025)
Background: Preterm labour (PTL), defined as childbirth occurring before 37 weeks of gestation, is a leading cause of neonatal morbidity and mortality. This study aimed to investigate the socioeconomic and obstetric risk factors associated with PTL among pregnant women in Wasit General Hospitals, Iraq. Methods: A quantitative, descriptive study design was employed, with data collected from 100 pregnant women admitted to six hospitals in Wasit Province between May 25 and September 10, 2024. Participants were selected using purposive sampling and completed a structured questionnaire covering demographic, socioeconomic, and obstetric factors. Statistical analysis included descriptive statistics and chi-square tests to assess associations. Results: - Demographics: Most participants were aged 21–25 years (43%), had low education levels (78% illiterate/primary school), and lived in extended families (58%). - Obstetric History: Multiparity (66%), irregular antenatal visits (71%), and overweight/obesity (72%) were prevalent. Infections (vaginitis: 37%, UTI: 30%) and prior preterm birth (15%) were significant risk factors. - Risk Distribution: 57% of women were low-risk, 36% moderate-risk, and 7% high-risk for PTL. - Associations: Significant associations were found between PTL risk and age (*p* < 0.001), economic status (*p* < 0.001), and family size (*p* < 0.001). Conclusion: The study highlights the interplay of socioeconomic and obstetric factors in PTL, with younger age, low education, economic instability, and infections being key contributors. Targeted interventions, such as improved antenatal care and health education, are recommended to mitigate PTL risks in this population.